Determinants of in Production Factors as Indicators of Farm Structure Transformations in Highly Fragmented Agriculture - Ostromęcki, Artur; Zając, Dariusz; Mantaj, Andrzej (Olsztyn Economic Journal, 2012)
This paper presents the relationship between changes in production factors and selected production conditioning. Due to the type of data used, the analysis was based on a Kruskal-Wallis statistical test and the x2 test. This analysis determined the farmer's most manageable processes of change and their direct factors. The research findings should be used to develop effective instruments of regional policy towards agribusiness.